A PP6-Type Phosphatase Holoenzyme Directly Regulates PIN Phosphorylation and Auxin Efflux in Arabidopsis([C])([W]) - Dai, Mingqiu (American Society of Plant Biologists, 2012)
The directional transport of the phytohormone auxin depends on the phosphorylation status and polar localization of PIN-FORMED (PIN) auxin efflux proteins. While PINIOD (PID) kinase is directly involved in the phosphorylation of PIN proteins, the phosphatase holoenzyme complexes that dephosphorylate PIN proteins remain elusive. Here, we demonstrate that mutations simultaneously disrupting the function of Arabidopsis thaliana FyPP1 (for Phytochrome-associated serine/threonine protein phosphatase1) and FyPP3, two homologous genes encoding the catalytic subunits of protein phosphatase6 (PP6), cause elevated accumulation of phosphorylated PIN proteins, correlating with a basal-to-apical shift in subcellular PIN localization. The changes in PIN polarity result in increased root basipetal auxin transport and severe defects, including shorter roots, fewer lateral roots, defective columella cells, root meristem collapse, abnormal cotyledons (small, cup-shaped, or fused cotyledons), and altered leaf venation. Our molecular, biochemical, and genetic data support the notion that FyPP1/3, SAL (for SAPS DOMAIN-LIKE), and PP2AA proteins (RCN1 [for ROOTS CURL IN NAPHTHYLPHTHALAMIC ACID1] or PP2AA1, PP2AA2, and PP2AA3) physically interact to form a novel PP6-type heterotrimeric holoenzyme complex. We also show that FyPP1/3, SAL, and PP2AA interact with a subset of PIN proteins and that for SAL the strength of the interaction depends on the PIN phosphorylation status. Thus, an Arabidopsis PP6-type phosphatase holoenzyme acts antagonistically with PID to direct auxin transport polarity and plant development by directly regulating PIN phosphorylation.